2018
DOI: 10.1038/s41598-018-26319-2
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1 inhibition by MS-275 in mesothelial cells limits cellular invasion and promotes MMT reversal

Abstract: Peritoneal fibrosis is a pathological alteration of the peritoneal membrane occurring in a variety of conditions including peritoneal dialysis (PD), post-surgery adhesions and peritoneal metastases. The acquisition of invasive and pro-fibrotic abilities by mesothelial cells (MCs) through induction of MMT, a cell-specific form of EMT, plays a main role in this process. Aim of this study was to evaluate possible effects of histone deacetylase (HDAC) inhibitors, key components of the epigenetic machinery, in coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Additionally, the mesothelial cells (MCs) isolated from effluent of peritoneal dialysis (PD) patients were treated with MS-275, a HDAC1-3 inhibitor, and downregulated mesenchymal markers including TGF-β1 to promote EMT reversal. Further genetic silencing experiments confirmed that HDAC1 played a major role in EMT reversal 23 . Combined with these findings, our experiments suggested that TGF-β1 was the important downstream target of HDAC5-regulated EMT in diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, the mesothelial cells (MCs) isolated from effluent of peritoneal dialysis (PD) patients were treated with MS-275, a HDAC1-3 inhibitor, and downregulated mesenchymal markers including TGF-β1 to promote EMT reversal. Further genetic silencing experiments confirmed that HDAC1 played a major role in EMT reversal 23 . Combined with these findings, our experiments suggested that TGF-β1 was the important downstream target of HDAC5-regulated EMT in diabetic kidney disease.…”
Section: Discussionmentioning
confidence: 81%
“…20 Moreover, in MCs isolated from peritoneal effluent of PD patients who underwent EMT in vivo, then in a model of PDF exposure in vitro, HDAC1 was also highly expressed and associated with the decrease of nuclear histone H3 acetylation. 66 Blockade of HDAC1 with MS-275 rescued the acetylation profile on the E-cadherin promoter and downregulated Snail levels, which further prevented MCs and reversed EMT. 66 Io et al administered SAHA, a nonspecific HDAC inhibitor, to verify its effect on the progression of PF in a mouse model established by intraperitoneal injection of CG.…”
Section: Epigenetic Modulation During Pdmentioning
confidence: 99%
“…66 Blockade of HDAC1 with MS-275 rescued the acetylation profile on the E-cadherin promoter and downregulated Snail levels, which further prevented MCs and reversed EMT. 66 Io et al administered SAHA, a nonspecific HDAC inhibitor, to verify its effect on the progression of PF in a mouse model established by intraperitoneal injection of CG. 67 SAHA increased levels of histone acetylation in injured peritoneum and suppressed peritoneal thickening and mediated upregulation of BMP-7 expression.…”
Section: Epigenetic Modulation During Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…When fibrosis occurs, there is a mesothelial to mesenchymal transition (MMT) which causes invasion. MS-275 is a specific class-I HDAC inhibitor which inhibits cellular invasion and promotes MMT reversal in peritoneal fibrosis [268]. HDACi are also used in various preclinical models of immunological diseases such as EAE (experimental autoimmune encephalomyelitis), asthma, and rheumatoid arthritis [269, 270].…”
Section: Regulation Of Mef-2mentioning
confidence: 99%